2020
DOI: 10.1021/acs.analchem.9b05753
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Isomerism Directed Electrochemical Sensing

Abstract: We report the independent role of isomerism of secondary sphere substituents over their nature, a factor often overlooked in molecular electrocatalysis pertaining to electrochemical sensing, by establishing that isomerism redefines the electronic structure at the catalytic reaction center via geometrical factors. UV–vis spectroscopy and X-ray photoelectron spectroscopy suggest that a substituent’s isomerism in molecular catalysts conjoins molecular planarity and catalytic activation through competing field eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…This suggests that for the direct As (III) oxidation, isomerism of functionality does not change the overall reaction mechanism but it can influence the rate-limiting step. Since direct As (III) oxidation on these molecular catalysts follow an EC mechanism wherein Co (III) is the active intermediate, the higher activity of β-isomer over its α counterpart originates from the isomerism induced oxidative activation of catalytic metal centre in the former as explained earlier [22]. The β isomer's sensor response towards direct As (III) oxidation demonstrated good reproducibility and high cyclic stability and FTIR spectral response of the β isomer electrode showed a durable sensing architecture, Figure 4.…”
Section: Isomerism Directed Electrochemical Sensingmentioning
confidence: 88%
See 4 more Smart Citations
“…This suggests that for the direct As (III) oxidation, isomerism of functionality does not change the overall reaction mechanism but it can influence the rate-limiting step. Since direct As (III) oxidation on these molecular catalysts follow an EC mechanism wherein Co (III) is the active intermediate, the higher activity of β-isomer over its α counterpart originates from the isomerism induced oxidative activation of catalytic metal centre in the former as explained earlier [22]. The β isomer's sensor response towards direct As (III) oxidation demonstrated good reproducibility and high cyclic stability and FTIR spectral response of the β isomer electrode showed a durable sensing architecture, Figure 4.…”
Section: Isomerism Directed Electrochemical Sensingmentioning
confidence: 88%
“…When α and β -NO 2 isomeric molecules were employed for the direct oxidation of As (III), the latter has been found to outperform the former in terms of activity and stability. Hydrodynamic voltammetry revealed that the overall number of electrons transferred is 2 in both the cases, however, the catalytic rate constants were significantly amplified in the case of β-NO 2 isomer compared to the α-NO 2 isomer [22]. Compared to the 'α' isomer, the 'β' isomer demonstrated high sensitivity and~170 mV reduction (at 0.15 mA/cm 2 ) in driving force towards the multi electron As (III) oxidation ( Figure 3); thus making it a viable candidate for water remediation and arsenic detection with detection limit close to the WHO guidelines [22].…”
Section: Isomerism Directed Electrochemical Sensingmentioning
confidence: 93%
See 3 more Smart Citations